Усталені поперечні коливання шару з масивним тілом - Микитюк, О.; Сухорольський, М. (Видавництво Національного університету "Львівська політехніка", 2004)
Розглядається задача про усталені коливання пружного шару з абсолютно твердим тілом. Побудова числового розв'язку відповідної мішаної задачі для системи рівнянь теорії пружності Грунтується на секвенціальному поданні узагальнених функцій та апроксимації функцій послідовностями узагальнених частинних сум рядів Фур'є. The problem of stable oscillations of the elastic layer with the absolutely solid is considered. The constructing of the numerical solution of the corresponding mixed problem for the system of equation of the theory of elasticity is based on the sequential presentation of the generalized functions and function approximation by means of sequences generalized partial sums of Fourier series.
Stable transversal oscilations of the layer with massive body
Keywords: теорія пружності; коливання шару; секвенціальне подання узагальнених функцій; ряди Фур'є; theory of elasticity; oscillations of the layer; sequential presentation of the generalized functions; Fourier series